1998
DOI: 10.1074/jbc.273.44.28642
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Alanine for Serine 250 in the Murine Fatty Acid Transport Protein Inhibits Long Chain Fatty Acid Transport

Abstract: The murine fatty acid transport protein (FATP) was identified on the basis of its ability to facilitate uptake of long chain fatty acids (LCFAs) when expressed in mammalian cells. To delineate FATP domains important for transport function, we cloned the human heart FATP ortholog. Comparison of the human, murine, and yeast amino acid sequences identified a highly conserved motif, IYTSGTTGXPK, also found in a number of proteins that form adenylated intermediates. We demonstrate that depletion of intracellular AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
67
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 40 publications
5
67
0
Order By: Relevance
“…Importantly, the LCFA pool was not increased but also similarly reduced, consistent with the model that the ACSL activity of FATP1 is critical for facilitating LCFA influx. These results are in agreement with the observations of StuhlsatzKrouper, Bennett, and Schaffer (43), who have shown that mutation of FATP1 serine 250 to alanine not only reduced the catalytic activity of the enzyme but also eliminated LCFA influx, implying that catalysis is functionally linked to uptake. In contrast to FATP1 kd adipocytes, FATP4 kd adipocytes revealed no change in basal or insulin-stimulated cellular fatty acid influx.…”
Section: Discussionsupporting
confidence: 93%
“…Importantly, the LCFA pool was not increased but also similarly reduced, consistent with the model that the ACSL activity of FATP1 is critical for facilitating LCFA influx. These results are in agreement with the observations of StuhlsatzKrouper, Bennett, and Schaffer (43), who have shown that mutation of FATP1 serine 250 to alanine not only reduced the catalytic activity of the enzyme but also eliminated LCFA influx, implying that catalysis is functionally linked to uptake. In contrast to FATP1 kd adipocytes, FATP4 kd adipocytes revealed no change in basal or insulin-stimulated cellular fatty acid influx.…”
Section: Discussionsupporting
confidence: 93%
“…Subsequent studies have demonstrated that the overexpression of FATP1, FATP2, or FATP4 in COS1 cells increases cell-associated acyl-CoA synthetase activities (11,26,27). Moreover, mutation of serine 250 to alanine significantly reduced fatty acid uptake, suggesting that esterification of fatty acids is coupled to influx (28). The current study was undertaken to evaluate the catalytic properties of the FATP1 acyl-CoA synthetase reaction.…”
Section: Discussionmentioning
confidence: 95%
“…Antibodies to native FATP1 sequences were generated as previously described (2,14). Cell culture reagents were from Invitrogen.…”
Section: Methodsmentioning
confidence: 99%
“…Expression Constructs-PCR was used to insert amino-terminal HA, amino-terminal Myc, and carboxyl-terminal FLAG tags into ⌬U3FATP1 or ⌬U3FATP1s250a mutant retroviral constructs (14). Retrovirus was generated and used to transduce cells as previously described (17).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation